New evidence on the labor market effects of scope of practice laws for physicians and nurse practitioners. - Bhai, Moiz; Mitchell, David T. (Contemporary Economic Policy, 2025)
We explore the labor market effects of state‐level scope of practice (SOP) reform for nurse practitioners that grants full practice authority (FPA) on the earnings and labor supply decisions of physicians and nurse practitioners. We employ a difference‐in‐differences research design using data from the American Community Survey between 2010 and 2019 to find that SOP laws granting FPA increase earnings of nurse practitioners and have some impacts on their labor supply. However, we find no effects on the earnings of physicians. To examine mechanisms, we use aggregated Medicare data from the Dartmouth Atlas to show no change on physician reimbursements.